The Influence of Factors Related to Safety Culture Maturity on Offshore Drilling Operations in Saudi Arabia - Lumanauw, Jimmy; Erislan, Erislan; Irianto, Hari Eko; Sugiarto, Sugiarto (Syntax Corporation, 2025)
Offshore drilling operations are a high-risk activity that requires a work safety system that is not only compliance-based, but also supported by a mature safety culture. Safety culture maturity is an important indicator in assessing the extent to which safety values have been embedded and applied thoroughly in the work environment. This study aims to analyze the influence of five groups of factors on the level of maturity of safety culture, namely: organizational and managerial factors, individual and culture, communication and participation, technical and operational, and external factors. The research was conducted on three jack-up rigs owned by COSL Drilling Saudi Limited in Saudi Arabia, involving 300 respondents from various levels of work. The quantitative approach was used with stratified random sampling techniques and data analysis was carried out using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results showed that all independent factors had a significant influence on safety culture maturity, with individual and cultural factors as the most dominant factors. This research contributes to identifying priority areas for strengthening safety culture to build a proactive, adaptive, and sustainable work safety system in the offshore drilling industry.